Automatic Ceiling Fan Controller Based On Temperature Sensor And Reactivated System - Nur Mohd Fadzli Bin Nordzi, Nur Mohd Fadzli (2010)
This study aims to make adjustment or improvement towards common ceiling fan operation that widely use centrifugal switch as a controller. The objective of this project is to create reliable automatic fan controller and human detection system especially for the user.